Neurological Adverse Effects of Antipsychotics in Children and Adolescents. Issue 6 (December 2015) - Garcia-Amador, Margarita; Merchán-Naranjo, Jessica; Tapia, Cecilia; Moreno, Carmen; Castro-Fornieles, Josefina; Baeza, Inmaculada; de la Serna, Elena; Alda, José A.; Muñoz, Daniel; Andrés Nestares, Patricia; Cantarero, Carmen Martínez; Arango, Celso
Abstract : Objective: The aim of this study was to evaluate demographic, clinical, and treatment factors that may impact on neurological adverse effects in naive and quasi-naive children and adolescents treated with antipsychotics. Methods: This was a 1-year, multicenter, observational study of a naive and quasi-naive pediatric population receiving antipsychotic treatment. Two subanalyses were run using the subsample of subjects taking the 3 most used antipsychotics and the subsample of antipsychotic-naive subjects. Total dyskinesia score (DyskinesiaS) and total Parkinson score (ParkinsonS) were calculated from the Maryland Psychiatric Research Center Involuntary Movement Scale, total UKU-Cognition score was calculated from the UKU Side Effect Rating Scale. Risk factors for tardive dyskinesias (TDs) defined after Schooler-Kaine criteria were studied using a logistic regression. Results: Two hundred sixty-five subjects (mean age, 14.4 [SD, 2.9] years) with different Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition Axis I disorders were recruited. DyskinesiaS ( P < 0.001) and ParkinsonS ( P < 0.001) increased at 1-year follow-up. Risperidone was associated with higher increases in DyskinesiaS compared with quetiapine ( P < 0.001). Higher increases in ParkinsonS were found with risperidone ( P < 0.001) and olanzapine ( P = 0.02) compared with quetiapine. Total UKU-Cognition Score decreased at follow-up. Findings were also significant when analyzing antipsychotic-naive subjects. Fifteen subjects (5.8%) fulfilled Schooler-Kane criteria for TD at follow-up. Younger age, history of psychotic symptoms, and higher cumulative exposure time were associated with TD at follow-up. Conclusions: Antipsychotics increased neurological adverse effects in a naive and quasi-naive pediatric population and should be carefully monitored. Risperidone presented higher scores in symptoms of dyskinesia and parkinsonism. Quetiapine was the antipsychotic with less neurological adverse effects. Younger subjects, psychosis, and treatment factors predicted an increased risk of TD.